“Do quartel pra dentro” : hierarquia e machismo nos cursos de formação na Polícia Militar de Estado de Sergipe - Prata, Luciana Tourinho (2023)
The present dissertation has as its object the intersection between military authority and Chauvinist Male in the training courses of the Military Police of the State of Sergipe, through the report of the experiences lived by the military police. I try to analyze military waits regarding various processes of hierarchical and gender subordination to which they tend to be attended during training and career improvement courses within a military institution. Training and improvement courses, in this sense, are analyzed as rites of passage, necessary to incorporate what authors such as Celso Castro call the “Ethos of the Warrior”, in addition to constituting, from the analytical point of view, as a kind of of microcosm through which we can understand important aspects around gender relations in the Military Police. For this, I refer to what Donna Haraway calls “localized knowledge”. In other words, from my own experience as a woman and member of the Military Police of the State of Sergipe, I try to establish a dialogue with my interlocutors and understand experiences that we share inside the barracks. Throughout the research I used autoethnography and dialogue with members of the corporation in which I participate. I believe that if this perspective is not enough to account for all the complexity surrounding a topic, but at least it can shed light on aspects not problematized by approaches that claim to be behind a supposed “scientific objectivity” and that present themselves as localized knowledge, disinterested to any geopolitical location. In this way, I try to better understand how the relations of power, authority and machismo are experienced by the military police “from the barracks to the inside”.